Case Report: Spontaneous cholecystocutaneous fistula, a rare cholethiasis complication [version 1; referees: 3 approved] - Nunzio Maria Angelo Rinzivillo; Riccardo Danna; Vito Leanza; Melissa Lodato; Salvatore Marchese; Francesco Basile; Guido Nicola Zanghì (F1000Research, 2017)
One of the most unusual complications in cholethiasis is spontaneous cholecystocutaneous fistula, which has only been reported a few times in the literature.  We report the case of a 76 year old man who presented with a right hypochondrium subcutaneous abscess, with pain evoked through palpation.  No comorbidity in the patient’s medical history were noted.   Confirmation of cholecystocutaneous fistula was made using the proper diagnostic process, which is computed tomography with contrast media, followed by hepatobiliary MRI. This confirmed the presence of a fistulous pathway between the gallbladder and the skin.  The patient underwent cholecystectomy surgery and open laparotomy with en block aponeurotic muscle, skin and fistula orifice excision.